Analysis of the Environmental Status of Nagykálló Subregion - Kozmáné Petrilla, Gréta (Acta Agraria Debreceniensis, 2005)
The third smallest region of Szabolcs-Szatmár-Bereg county is the Nagykálló subregion. Its territory is 377 km2 and its inhabitants number 32.526. Due to the fact that industrial development arrived late, the environmental status of this subregion was saved from serious ecological degradation. The quality of the environment shows a reasonable picture in many respects, comparing to the general survey of the country. The air quality of the region can be qualified as acceptable. Leaving some critical points out of consideration, it is better than the national average. It is favourable from the human environment point of view that the region is free of extremes, and has a balanced climate. The supply of drinking water is above 95%, and the remainsing water requirements are supplied by artesian wells. The water supply network is fully extended in the subregion. The most significant environmental noise source is traffic, including public road traffic, which causes a problem in the town of Nagykálló. The situation of the collection, transportation, and placement of the settlement’s solid wastes show a similar picture to the status of the country. The environmental status of the region is included in the SWOT analysis.